CONTRIBUTION TO THE STUDY AND SIZING OF A PHOTOVOLTAIC SYSTEM FOR AGRICULTURAL IRRIGATION - Islem Eddine Khadraoui (My University, 2025)
This study focuses on designing a standalone photovoltaic irrigation system for a site in Souk Ahras, Algeria. It aims to meet agricultural water needs using solar energy, replacing conventional sources. Manual sizing and PVsyst simulation were performed to evaluate hydraulic and electrical requirements. The system, using a Lowara 12GS40 pump and 14 Jinko 440 Wp modules, achieved 97.2% of annual water needs with strong alignment between manual and simulated results. ----------------------------------------------------------------------------- تركّز هذه الدراسة على تصميم نظام ري مستقل يعمل بالطاقة الشمسية في موقع بولاية سوق أهراس، الجزائر. يهدف النظام إلى تلبية احتياجات المياه الزراعية باستخدام مصدر متجدد بديل للمصادر التقليدية. تم تنفيذ عملية التقييم من خلال حسابات يدوية ومحاكاة باستخدام برنامج مختص، لتحديد المتطلبات من حيث الجوانب الهيدروليكية والكهربائية. يعتمد النظام على مضخة طرد مركزي مناسبة تغذّيها 14 لوحة شمسية عالية القدرة، وقد حقق تغطية بنسبة 97.2٪ من الاحتياجات السنوية للمياه، مع توافق كبير بين النتائج اليدوية ونتائج المحاكاة ----------------------------------------------------------------------------- Cette étude porte sur le dimensionnement d’un système de pompage photovoltaïque autonome pour un site à Souk Ahras, Algérie. Elle vise à répondre aux besoins en eau agricoles grâce à l’énergie solaire. Des calculs manuels et une simulation PVsyst ont permis d’évaluer les besoins hydrauliques et électriques. Le système, utilisant une pompe Lowara 12GS40 et 14 modules Jinko de 440 Wc, couvre 97,2 % des besoins annuels avec une bonne cohérence des résultats.
Keywords: : photovoltaic; irrigation; solar energy; PVsyst; water pumping.; :الطاقة الشمسية، الري، ضخ المياه، النظام الكهروضوئي، المحاكاة; photovoltaïque; énergie solaire; pompage